Noble Cause Corruption Revisited: Toward a Structured Research Approach. (3rd July 2017) - van Halderen, Robin Christiaan; Kolthoff, Emile
Abstract : Police officers sometimes violate laws and internal procedures to the benefit of society or the police organization. In the literature, this type of behavior is commonly termed noble cause corruption and framed as resulting from a police officer's moral deliberations. Although the phenomenon has received scholarly attention for over three decades, surprisingly little progress has been made in empirical research and theoretical development. Research on noble cause corruption is still in an exploratory phase, partly due to the absence of a clear and common definition, and the complexity of operationalizing the concept. Task-related rule-breaking behavior, a more refined alternative concept, is introduced here to encourage a systematic and interdisciplinary research approach. It is contrasted to 55 closely related concepts used in various scientific disciplines. The closely related concepts are clustered and mapped. Task-related rule-breaking behavior is mostly connected to concepts such as organizational crime, state crime, and unethical pro-organizational behavior. The research on these closely related concepts contributes to a deeper understanding of task-related rule-breaking behavior, and shows how research on the phenomenon is valuable for studies on related themes in diverse scientific domains.